Seasonal variations in the species diversity of planktonic rotifers in the pertek region of Keban Dam Lake, Turkey - Tellioglu, Ayda; Akman, Fatih (Oikos Publ Inc, 2007)
We collected rotifers during one year (2002-2003) from three different sites in the Pertek region of Keban Dam Lake. In total, 20 species belonging to 15 genera of I I eurotatorian families were identified. The highest total rotifer abundance (346,667 individuals/m(3)) was recorded in December, while the lowest total abundance (7,640 individuals/m(3)) was seen in February. The densities of most rotifer species were highest in the spring months. Species richness was related directly to rotifer abundance. Rotifers were dominated numerically by two species, Polyarthra remata and Polyarthra vulgaris (14.9% and 14.4% respectively). Species abundance was positively related to temperature.
Keywords: Zooplankton Community; Temperature